SUN-467 Vitamin B(6) and N-Acetylcysteine Protect Hypothalamic Neurons from Bisphenol A-Mediated Induction of Neuropeptide Y Gene Expression - Loganathan, Neruja (J Endocr Soc, 2019)
Bisphenol A (BPA), a ubiquitous endocrine disrupting chemical with estrogenic properties, disrupts reproductive function, but is also considered an obesogen. Potential targets of BPA are the neuropeptide Y (NPY) neurons of the hypothalamus as specific sub-populations act to increase food intake, while others regulate the hypothalamic-pituitary-gonadal axis, thereby coordinating reproduction. We previously found that BPA upregulated Npy mRNA expression in four hypothalamic cell lines (mHypoA-59, mHypoA-2/12, mHypoE-41, mHypoE-42) across 24 hours, potentially contributing to the obesogenic effect of BPA, whereas it decreased Npy expression in two cell lines (mHypoE-46, mHypoE-44). These differential responses may reflect cell-specific differences that exist within hypothalamic NPY neurons functioning to coordinate either energy balance or reproduction. We also found that BPA increased markers of neuroinflammation (Il6, Tnfα, Il10) and inducible nitric oxide synthase (iNos) in mHypoA-59 and mHypoE-41 cells. Therefore, we hypothesized that BPA alters Npy expression through induction of neuroinflammation or oxidative stress. Inhibition of the NFkB inflammatory pathway (PS1145) or iNOS (L-NAME or TRIM) did not abrogate the BPA-mediated Npy induction, demonstrating that inflammation and iNOS do not appear to upregulate Npy. Interestingly, treatment of the mHypoA-59 cells with BPA in an antioxidant-rich media, neurobasal A (NBA), mitigated the BPA-induced increase in Npy. A comparison of NBA and Dulbecco’s modified Eagle’s medium revealed three major advantages to NBA: the presence of vitamin B12 and bio-available forms of vitamin B(6) and L-cysteine. Treatment with BPA in the presence of N-acetylcysteine or vitamin B(6), but not vitamin B(12), demonstrated an attenuation in the BPA-mediated upregulation of Npy mRNA, suggesting that these antioxidant species in NBA potentially protect the cells from the detrimental effects of BPA. On another front, since BPA is considered an estrogen mimic in other cell types, we also investigated the involvement of estrogen receptors. BPA altered the ERβ/ERα ratio, decreasing it in the mHypoA-59 and mHypoE-41 cells, while increasing it in the mHypoE-46 cells due to a substantial decrease in ERα mRNA levels. Pretreatment with ERα or ERβ inhibitors (MPP, PHTPP, ICI182) did not alter the BPA-mediated upregulation of Npy, suggesting estrogen receptor-independent mechanisms mediate the increase in Npy. Future experiments will investigate whether estrogen receptors, particularly ERβ, mediate the BPA-induced downregulation of Npy in specific sub-populations. Overall, these experiments illustrate the mechanisms underlying the differential regulation of Npy by BPA in diverse neuronal sub-populations that may carry out distinct functions.